Linguistic Aspects of Translation, Localization, and Transcreation in Advertising Slogans from Slovene into Serbian: A Case Study with MA Translation Students - Kučiš, Vlasta; Prodanović Stankić, Diana (Slavia Centralis, 2026)
The paper discusses significance and characteristics of localization and transcreation in the translation of advertising slogans from Slovenian into Serbian by analyzing translation solutions of translation students at the Faculty of Philosophy in Novi Sad. Based on the analysis of the translations, we discovered that the students demonstrate appropriate linguistic competences, but do not distinguish between translation, localization and transcreation strategies. The case study reveals the need for a more extensive pedagogical focus on pragmatic and semiotic functions of advertising language and the importance of cultural specificity and creativity in the translation of advertising slogans. The research results indicate the need for a translational and professional discussion about the limits and intersections of translation, localization and transcreation in a global, multilingual and market-oriented society.